Parking goes mobile: a research proposal - Ferreira, Sara (2014)
This paper presents a research proposal to study the process to create a mobile application considering important restrictions on the development schedule and on the team size. The objective of the application is to help citizens to find parking spots in urban context. A theoretical framework is presented, based on several dimensions, such as the software development approach, the different mobile application’s types and its implications, the specific design issues for mobile applications, the technological frameworks that could be used, and an analysis of the existent applications that have similar objectives. The research proposal is described: its objectives, the research question, and a discussion on technical options related with the dimensions of the theoretical framework. The following steps of the project are outlined.